PENGARUH UKURAN PERUSAHAAN DAN KEPEMILIKAN ASING TERHADAP NILAI PERUSAHAAN - Lucky Adhika Wardana; Apit Susanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to obtain empirical evidence regarding the influence of independent variables, namely, profitability, liquidity, asset growth, company size, institutional ownership, managerial ownership, and foreign ownership, while the dependent variables in this case are company value. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for a 5-year research period, from 2017 to 2021. The sampling used in this study was using purposive sampling techniques. With this method, there are 60 companies that meet predetermined criteria. So that 240 data were obtained that can be used as research samples. Then, in this study using the multiple regression method to analyze the data. The results of this study show that profitability, asset growth and institutional ownership affect the value of the company. If the profitability is higher, the value of the company will increase and the higher the growth of assets, the value of the company will decrease. But on the contrary, liquidity, company size, managerial ownership and foreign ownership have no effect on the value of the company.